A summer's dietry study for a family of four - McRae, Alma (My University, 1906)
Introduction: The thesis is an actual experiment conducted in a family consisting of four people. The experiment began June 24, 1905, and ended September 2, 1905. During the entire time menus were kept of each meal, and for three periods of four days each, the actual weight and cost of the food eaten was noted. From the weight of the food recorded the calorie value per capita and the nutritive ratio has been figured for each meal of the three series. The first of these periods is from June 24 to June 28 ; the second from July 29 to August 2; the third from August 30 to September 3. The days covered in each case are Saturday, Sunday, Monday, and Tuesday; the diet of these days is a fair representation of the diet during the Summer. The locality is the eastern part of the state in a small country town. The family kept a garden, therefore the vegetables eaten did not figure as expense; chickens were also kept so only occasionally were the chickens eaten purchased. One quart of milk was bought daily at five cents per quart. The cost of the milk has been divided among the meals where it was used in the menus. Its entire cost was always included. The general health of the family was good at the beginning, and was also good at the end of the experiment.
Citation: McRae, Alma. A summer's dietry study for a family of four. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Home Economics; Diet; Kansas; Theses